Efficient preclinical treatment of cortical T cell acute lymphoblastic leukemia with T lymphocytes secreting anti-CD1a T cell engagers - Pablo Menendez; Diego Sánchez Martínez; Néstor Tirado; Alba Martínez-Moreno; Anaïs Jiménez-Reinoso; Víctor M Díaz; Marina García-Peydró; Oana Hangiu; Laura Díez-Alonso; Ángela Albitre; Petronila Penela; Maria L Toribio; et al. (Journal for ImmunoTherapy of Cancer)
Background The dismal clinical outcome of relapsed/refractory (R/R) T cell acute lymphoblastic leukemia (T-ALL) highlights the need for innovative targeted therapies. Although chimeric antigen receptor (CAR)-engineered T cells have revolutionized the treatment of B cell malignancies, their clinical implementation in T-ALL is in its infancy. CD1a represents a safe target for cortical T-ALL (coT-ALL) patients, and fratricide-resistant CD1a-directed CAR T cells have been preclinically validated as an immunotherapeutic strategy for R/R coT-ALL. Nonetheless, T-ALL relapses are commonly very aggressive and hyperleukocytic, posing a challenge to recover sufficient non-leukemic effector T cells from leukapheresis in R/R T-ALL patients.Methods We carried out a comprehensive study using robust in vitro and in vivo assays comparing the efficacy of engineered T cells either expressing a second-generation CD1a-CAR or secreting CD1a x CD3 T cell-engaging Antibodies (CD1a-STAb).Results We show that CD1a-T cell engagers bind to cell surface expressed CD1a and CD3 and induce specific T cell activation. Recruitment of bystander T cells endows CD1a-STAbs with an enhanced in vitro cytotoxicity than CD1a-CAR T cells at lower effector:target ratios. CD1a-STAb T cells are as effective as CD1a-CAR T cells in cutting-edge in vivo T-ALL patient-derived xenograft models.Conclusions Our data suggest that CD1a-STAb T cells could be an alternative to CD1a-CAR T cells in coT-ALL patients with aggressive and hyperleukocytic relapses with limited numbers of non-leukemic effector T cells.